2017
DOI: 10.1111/pere.12194
|View full text |Cite
|
Sign up to set email alerts
|

Males benefit twice—The influence of equity on affective and physical attraction in couples

Abstract: We examined whether relationship satisfaction mediates the association between perceptions of equity in central areas of a relationship (feelings and attractiveness) and the experience of sexuality in a sample of 93 couples. Results reveal that greater levels of an individual's own relationship satisfaction significantly predict greater levels of an individual's affective and physical sexual attraction. Furthermore, findings also provide some support for the mediating role of relationship satisfaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…For instance, previous research on sociosexuality has shown that relationship agreement moderates the negative association between unrestricted sociosexuality and relationship quality, independent of gender (Rodrigues et al, 2017). Studies on dyadic data have examined whether there are congruencies or discrepancies in relationship aspects, e.g., using polynomial regression analyses (Quittschalle & Herzberg, 2017). Further research should address this issue.…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%
“…For instance, previous research on sociosexuality has shown that relationship agreement moderates the negative association between unrestricted sociosexuality and relationship quality, independent of gender (Rodrigues et al, 2017). Studies on dyadic data have examined whether there are congruencies or discrepancies in relationship aspects, e.g., using polynomial regression analyses (Quittschalle & Herzberg, 2017). Further research should address this issue.…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%